Blusas-verdes à beira-mar: mulheres integralistas - Santos (1932-1937) - Ferreira, Lilian Tavares de Bairros (2018)
The aim of this study is to discuss the participation of women in the Integralist movement in the city of Santos between 1932 and 1937. This thesis recovers stories from the feminist movement and women‘s fights in the harbor city of Santos. Also, it shows how the leaders of the Integralist movement perceived the possibility of engaging women among their militants. Thus, the Integralism tried to attract women with speeches about defending the family and Catholicism; in order to do so, they proposed that women would participate more effectively in the institutional politics by assigning functions to the group of women whom participated in the movement. In the development of this research, it was possible to observe that the Blusas-Verdes ("Green Blouses", as the women who acted within the Brazilian Integralist Action – AIB were called) operated in well-defined roles: activities in the educational segment, assistance to poor children, matters of public health and preventive medicine. Therefore, the aim of this research is to observe the relations and the development of women‘s participation in the Integralist center of Santos